Pengaruh Efektivitas Absensi Finger Print Terhadap Disiplin Pegawai Pada Kantor Kesyahbandaran Dan Otoritas Pelabuhan (KSOP) Kelas IV Bima - Dadang Zulfikar; Ety Kurniawati (Forum Kerjasama Pendidikan Tinggi, 2020)
This research aims to know the effect of the effectiveness of finger print attendance to the discipline of employees in the office of the Kesyahbandaran and Port Authority (KSOP) grade IV Bima. A population of 52 employees and samples amounted to 30 ASN employees and an associative research. Data collection technology is Library study, observation, and filling questionnaire. The research variables consist of free and bound variables. Variable free is the attendance of finger print (X) and the variable bound is the discipline of the employee (Y). Analysis techniques using quantitative analysis is a simple regression analysis, coherent correlation, and coherent determinations. Hypothesis test Using Test T. Hypothesis testing test results by using the test T obtained acount (2.064) greater than ttable (2.048) Thus it can be concluded that there is an influence between the effectiveness of finger print attendance to the discipline of employees in the office of the Seriation and Authority OF THE Port (KSOP) IV Grade Bima